2004
DOI: 10.4040/jkan.2004.34.8.1451
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Aggressive Behavior Among Nursing Home Residents with Cognitive Impairment

Abstract: Aggressive behavior among cognitively impaired nursing home residents is prevalent thus needs to be prevented and reduced. Along with environmental modification, educational programs for nursing staff and family caregivers need to be developed and implemented so that they can have extensive knowledge and skills to manage aggressive behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Resident pain can lead to patient disruptive and aggressive behavior, [39][40][41] which could lead to caregiver stress and burnout. 42,43 Moreover, as the detection of pain in the nursing home can be difficult, nurses and other staff members experience uncertainty about the treatment needs of each resident.…”
Section: Discussionmentioning
confidence: 99%
“…Resident pain can lead to patient disruptive and aggressive behavior, [39][40][41] which could lead to caregiver stress and burnout. 42,43 Moreover, as the detection of pain in the nursing home can be difficult, nurses and other staff members experience uncertainty about the treatment needs of each resident.…”
Section: Discussionmentioning
confidence: 99%
“…3 Other studies found that aggressive nursing home residents with CI had more pain than nonaggressive residents with CI. 4 Another study found that an increase in physically and verbally aggressive behaviors was associated with a decline in cognitive functioning over a 2-year period, 5 and significant associations between cognitive functioning and disruptive behaviors have also been observed in other studies. 6 Thus, it is possible that untreated pain and cognitive impairment are both underlying causes of disruptive behaviors.…”
Section: Analgesic Intake Cognitive Functioning and Disruptive Behamentioning
confidence: 84%
“…Oh et al . () compared aggressive with nonaggressive residents and found that aggressive residents had significantly more cognitive impairment and more pain and had stayed longer in the nursing home than nonaggressive residents.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that residents with a cognitive impairment show more aggressive behaviour (Talerico et al 2002, Voyer et al 2005, Testad et al 2007). Oh et al (2004) compared aggressive with nonaggressive residents and found that aggressive residents had significantly more cognitive impairment and more pain and had stayed longer in the nursing home than nonaggressive residents.…”
Section: Introductionmentioning
confidence: 99%